454-sequencingTM for the KEL, JR, and LAN blood groups - Wieckhusen, Carola; Bugert, Peter (Molecular typing of blood cell antigens, 2015)
The KEL (ISBT 006), JR (ISBT 032), and LAN (ISBT 033) blood group systems are defined by a complex genetics with a large number of exons, and numerous gene variants. In order to sequence the 53 coding exons and flanking intron regions of all three blood group genes we developed a next-generation-sequencing method using 454-sequencing™ on a Genome Sequencer (GS) Junior™ system. Multiplex analysis of eight individual DNA samples was achieved using molecular identifiers.
Im Titel ist TM hochgestellt
Gesehen am 06.07.2020